Endocrine and Metabolic Responses to Endurance Exercise Under Hot and Hypoxic Conditions - Yatsutani, Haruka; Mori, Hisashi; Ito, Hiroto; Hayashi, Nanako; Girard, Olivier; Goto, Kazushige (Frontiers in Physiology, 2020)
Purpose We explored the effect of heat stress during an acute endurance exercise session in hypoxia on the erythropoietin (EPO) response. Methods A total of 12 healthy males cycled at a constant workload (60% of the power output associated with their maximal oxygen uptake under each respective condition) for 60 min in three different environments: exercise under hot and hypoxia (H+H; fraction of inspiratory oxygen or FiO2: 14.5%, 32℃), exercise under hypoxia (HYP; FiO2: 14.5%, 23℃), and exercise under normoxia (NOR; FiO2: 20.9%, 23℃). After completing the exercise, participants remained in the chamber for 3 h to evaluate metabolic and endocrine responses under each environment. Changes in muscle oxygenation (only during exercise), blood variables, arterial oxygen saturation, and muscle temperature were determined up to 3 h after exercise. Results Serum EPO level was increased to similar levels in both H+H and HYP at 3 h after exercise compared with before exercise (P < 0.05), whereas no significant increase was found under NOR. No significant difference between H+H and HYP was observed in the serum EPO level, blood lactate level, or muscle oxygenation at any time (P > 0.05). Arterial oxygen saturation during exercise was significantly higher in H+H compared with HYP (P < 0.05). Exercise-induced serum growth hormone elevation was significantly greater in H+H compared with HYP (P < 0.05). Conclusion The serum EPO level increased significantly with endurance exercise in hypoxia. However, the addition of heat stress during endurance exercise in hypoxia did not augment the EPO response up to 3 h after completion of exercise.